2001
DOI: 10.1080/j003v13n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Use of Admission Criteria to Predict Performance of Students in an Entry-Level Master's Program on Fieldwork Placements and in Academic Courses

Abstract: The relationships among clinical outcomes, academic success, and predictors used to screen applicants for entrance into a Master in Occupational Therapy Program (MOT) were examined. The dependent variables were grade point average in occupational therapy courses (OT-GPA), client therapy outcomes at the clinic, and ratings of MOT students by Level II Fieldwork supervisors. Predictor variables included undergraduate GPA, scores on the Graduate Record Examination (GRE), and an essay. Both undergraduate GPA and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…The results of this study support previous research that indicated that the undergraduate GPA is a valid predictor of academic performance for students in a health science curriculum (Bridle, 1987;Howard & Jerosch-Herold, 2000;Kirchner et al, 2000;Kirchner & Holm, 1997;Lewis & Smith, 2002;Salvatori, 2001). The undergraduate GPA emerged as a significant correlate of not only the overall student OT academic average, but also of performance in the cognitiveneurological course.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study support previous research that indicated that the undergraduate GPA is a valid predictor of academic performance for students in a health science curriculum (Bridle, 1987;Howard & Jerosch-Herold, 2000;Kirchner et al, 2000;Kirchner & Holm, 1997;Lewis & Smith, 2002;Salvatori, 2001). The undergraduate GPA emerged as a significant correlate of not only the overall student OT academic average, but also of performance in the cognitiveneurological course.…”
Section: Discussionsupporting
confidence: 88%
“…A meta-analysis by Kuncel, Hezlett, and Ones (2001) determined that undergraduate GPA and performance on the Graduate Record Examination (GRE) are generally valid predictors of future academic performance in graduate school. This finding that past academic performance predicts future academic performance has been replicated in studies focused exclusively on OT graduate students (Kirchner & Holm, 1997;Kirchner, Stone, & Holm, 2000;Lysaght, Donnelly, & Villeneuve, 2009) as well as in studies on students in other related health care professions (Halberstam & Redstone, 2005;Jones, Simpkins, & Hocking, 2014;Keskula, Sammarone, & Perrin, 1995;Utzman, Riddle, & Jewell, 2007a). In addition, Bathje, Ozelie, and Deavila (2014) and Kirchner et al (2000) identified correlations between undergraduate GPA and GRE scores and future performance on fieldwork and academic performance at the graduate level among OT students.…”
Section: Literature Reviewmentioning
confidence: 50%
“…However, in an attempted replication of Kirchner and Holm's (1997) findings, Kirchner et al (2000) found no correlation between written essay scores and academic or fieldwork performance in a study of MOT students.…”
Section: Literature Reviewmentioning
confidence: 96%
“…There are a number of possible reasons for this. Academic grades are more likely to correlate with clinical performance when the grades are based on multiple rather than individual courses (Kirchner et al ., 2000). The fact that in this study, GPA was cumulative, based on an average of all courses to date, might explain why it was able to consistently predict student clinical performance in all behavioural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent results have been reported. While moderate positive relationships between academic grades and clinical performance ratings have been reported (Howard & Jerosch‐Herold, 2000; Kirchner, Stone & Holm, 2000), most studies have found no or only weak positive relationships between them (Best, 1994; Kirchner & Holm, 1997; Mann & Banasiak, 1985).…”
Section: Introductionmentioning
confidence: 98%